Pengembangan Media Ajar Website pada Materi Luas Bangun Datar Segiempat di Kelas V Sekolah Dasar - Aprilia, Nia; Zainil, Melva (TSAQOFAH, 2025)
This study is a development research aimed at creating a website-assisted learning medium for teaching the area of quadrilaterals to fifth-grade elementary school students in the city of Bukittinggi. The development model used was ADDIE (Analysis, Design, Development, Implementation, Evaluation), involving three elementary schools as the sample. Data analysis focused on three aspects: validity, practicality, and effectiveness of the media. Validation results showed that the media was highly valid, with a content validity score of 96.87%, language aspect 84.34%, and media aspect 87.5%. Practicality tests indicated that the media was very practical, based on responses from teachers at the trial school (90.65%) and students (88.41%), with similar results observed in the other two schools—teacher practicality scores were 93.75% and 96.87%, and student scores were 94.87% and 96.15%. Effectiveness tests demonstrated improved student learning outcomes, with effectiveness percentages of 84.70% at the trial school, 90.4% at the first school, and 93.07% at the second school, all falling into the "very effective" category. Based on these results, the website-based learning media developed in this study is declared valid, practical, and effective for supporting mathematics instruction on the topic of quadrilateral area in fifth-grade elementary school classes.